E-Learning Sebagai Solulusi Pembelajaran Dari Rumah Di Tengah Pandemi Covid-19 Di MTs. MAS Al-Jamiyatul Washliyah Lubuk Pakam - Herman Mawengkang; Sutarman Sutarman; Husain Husain; Mochamad Wahyudi (Jurnal Mantik, 2020)
Various information technology-based learning products were created to improve the quality of learning, one of which is online learning media known as e-learning. In addition, during the Covid 19 pandemic, which required learning from home, Mts.Mas Al-Jamiyatul Washliyah Lubuk Pakam was no exception. The use of the E-Learning application in PKM aims to help Mts.Mas Al-Jamiyatul Washliyah Lubuk Pakam in the process of teaching and learning activities. With this application, it is hoped that it can help problems faced by teachers and students outside of class hours, such as lack of communication time between teachers and students, searching for information about the material being taught, and of course to facilitate teachers in providing material to students. The result achieved is the availability of supporting applications for teaching and learning activities that can be obtained regardless of time and place. The conclusion with the existence of E-Learning is that it makes it easier for teachers to provide learning to students outside of class hours such as providing material, easiness in giving assignments and collecting assignments, exams, and facilitating value information.